First-principles study of strain-induced magnetic phase transition in iron with carrier doping - Susumu MINAMI; Yoshimasa ABE; Takahiro SHIMADA (Nihon Kikai Gakkai ronbunshu, 2023)
Magnetic materials exhibit various magnetic orders and are used in many magnetic and mechanical devices. In order to control and design magnetic ordering, the stability of the magnetic phase with mechanical strain has been reported in previous studies. In this study, based on the first-principles calculation, we investigate the stain dependence of the magnetic phase stability in iron with carrier doping. We find that the excess electron doping makes keeping the ferromagnetic (FM) phase for compressive strain loading in the (001) plane. On the other hand, hole doping leads to a multi-step strain-induced magnetic phase transition, and the spin spiral (SS) phase appears under the in-plane tensile strain. The 3d-orbital hybridization of up- and down-spin makes the hybridization gap, which is one origin of stabilized SS phase. FM phase under the in-plane strain and hole doping will be unstable due to the increasing 3d-orbital bands at Fermi energy; that is, SS phase will be the most stable state by the hybridization gap. The present study suggests that the excess electron/hole carrier doping and mechanical loading help to design a non-trivial magnetic phase in magnetic materials.